2014
DOI: 10.15376/biores.9.2.2960-2974
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Mechanical Evaluation of Bio-composites Based on Thermoplastic Starch and Wood Particles Prepared by Thermal Compression

Abstract: The present work inspects the preparation of bio-composites of cassava starch with particles of eucalyptus wood through the application of a novel method of thermal compression. Bio-composites with different amounts of wood particles (5 to 30%), with particle sizes of 4 and 8 mm, were obtained. Chemical and mechanical evaluation of these samples was carried out using optical microscopy, infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and the moisture absorption effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 26 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…) of rice starch showed a broad band centered at 3304 cm −1 due to the O–H stretching of starch. Other band at 2922 cm −1 was attributed by the C–H stretching vibrations of aliphatic groups, the band at 1643 cm −1 could be contributed by the O–H bending of water, bands at 1076 cm −1 and 835 cm −1 could be due to the C–O–C symmetric stretching, and the one at 1004 cm −1 was due to the C–O–H bending vibration . However, the FTIR spectrum of sAgNPs showed a similar spectrum as that of rice starch with a slight deviation in peaks associated with O–H functional group.…”
Section: Resultsmentioning
confidence: 89%
“…) of rice starch showed a broad band centered at 3304 cm −1 due to the O–H stretching of starch. Other band at 2922 cm −1 was attributed by the C–H stretching vibrations of aliphatic groups, the band at 1643 cm −1 could be contributed by the O–H bending of water, bands at 1076 cm −1 and 835 cm −1 could be due to the C–O–C symmetric stretching, and the one at 1004 cm −1 was due to the C–O–H bending vibration . However, the FTIR spectrum of sAgNPs showed a similar spectrum as that of rice starch with a slight deviation in peaks associated with O–H functional group.…”
Section: Resultsmentioning
confidence: 89%
“…The FTIR spectrum of the TPS‐RS also presents two bands, which cannot be observed in the native starch: 1743 and 1261 cm −1 . The presence of these bands has been reported previously, when the spectra of native starch and thermoplastic starch of cassava were compared . The first sign was attributed to compounds with carbonyl groups originating from a slight decomposition of the glycerol, and the second to the CH 2 ‐OH link of glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…uncompatibilised composites with wood fibre; Open circles (○) represent uncompatbilised composites with WF; Solid line is the trend-line for composites with wood fibre and dashed line is the trend-line for composites with WF [Agnantopoulou et al, 2012;Cobut et al, 2014;De Carvalho et al, 2002;Lomelí-Ramírez et al, 2014;Müller et al, 2014;Zhang et al, 2015] Muller et al used a mechanical strength model to quantify the interfacial adhesion between corn starch and wood fibres and found that such an interface demonstrated a stronger adhesion than that of PP and PLA [Müller et al, 2014]. Also, fourier-transform infrared spectroscopy (FTIR) analyses demonstrated compatibility between cassava starch and wood particles, which was attributed to the association by hydrogen bonding of OH groups [Lomelí-Ramírez et al, 2014]. Therefore, unlike the focus for PLA and PHA, research into TPS-based WPCs has been concentrated on understanding the reinforcing effects of various wood reinforcements rather than improving the interfacial adhesion through the addition of compatibilisers.…”
Section: Properties Of Tps-based Wpcsmentioning
confidence: 99%
“…It was also shown that the tensile strength of wood fibres/plasticised corn starch composites improved with increasing wood content then deteriorated when the wood content was above 40 wt% [Müller et al, 2014;Zhang et al, 2015]. Other types of starches, including potato [Cobut et al, 2014] and cassava starch [Lomelí-Ramírez et al, 2014], have also been used in composites. The addition of wood reinforcements to plasticised (using 30% glycerol) potato and cassava starch resulted in similar improvement in tensile strength and modulus as seen in corn starch-based WPCs [Cobut et al, 2014;Lomelí-Ramírez et al, 2014].…”
Section: Properties Of Tps-based Wpcsmentioning
confidence: 99%
See 1 more Smart Citation